Enhancing Students’ Critical Thinking and Mathematical Self-Concept Using an Autograph-Assisted Concept Attainment Model - Nurul Afni Sinaga; Eri Saputra; Rifaatul Husna; Nuraina; Erna Isfayani (FKIP Universitas Mataram, 2026)
The low level of students’ critical thinking skills and mathematical self-concept is influenced by the use of less effective learning models and the limited integration of technology in mathematics instruction. To address these issues, a concept attainment learning model assisted by Autograph software was implemented. This study aimed to examine whether the improvement of students’ critical thinking skills and mathematical self-concept through the concept attainment model assisted by Autograph was better than that achieved through conventional learning. This study employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The population consisted of twelfth-grade students at SMA Negeri 1 Tanah Jambo Aye. Data were collected through observations, interviews, tests, and non-test instruments. Test data were analyzed using the Mann–Whitney nonparametric test, while non-test data were analyzed using the independent sample t-test. The findings indicated that students taught using the concept attainment learning model assisted by Autograph demonstrated better improvement in critical thinking skills and mathematical self-concept compared to those taught through conventional learning.